The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/rs11030239
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing UAV–SfM 3D Model Accuracy in High-Relief Landscapes by Incorporating Oblique Images

Abstract: Complex landscapes with high topographic relief and intricate geometry present challenges for complete and accurate mapping of both lateral (x, y) and vertical (z) detail without deformation. Although small uninhabited/unmanned aerial vehicles (UAVs) paired with structure-from-motion (SfM) image processing has recently emerged as a popular solution for a range of mapping applications, common image acquisition and processing strategies can result in surface deformation along steep slopes within complex terrain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
164
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(183 citation statements)
references
References 80 publications
(157 reference statements)
17
164
0
2
Order By: Relevance
“…Aerial imaging, as applied in this study, may also be limited in capturing significantly occluded panicles [75]. The value of applying both nadir and oblique has been demonstrated in other UAS-based studies [76][77][78]. In our case multi-angle images should provide better view of panicles and likely lead to better detection.…”
Section: Discussionmentioning
confidence: 79%
“…Aerial imaging, as applied in this study, may also be limited in capturing significantly occluded panicles [75]. The value of applying both nadir and oblique has been demonstrated in other UAS-based studies [76][77][78]. In our case multi-angle images should provide better view of panicles and likely lead to better detection.…”
Section: Discussionmentioning
confidence: 79%
“…The advent of UAVs as carrier platforms of active and passive mapping sensors had a huge impact in the field of photogrammetry and remote sensing [14]. The introduction of Structure-from-Motion (SfM) and Dense Image Matching (DIM) techniques providing automatic orientation of entire image blocks and height estimates for every image pixel [15,16] has democratized image-based 3D mapping of topography and dramatically increased the achievable point densities [17,18]. The applicability of UAV-photogrammetry is further facilitated due to the existence of easy-to-use software solutions Remote Sens.…”
Section: Uav-borne Multimedia Photogrammetrymentioning
confidence: 99%
“…For example, if wanting to produce a fine spatial resolution map, or look at animal species relationship to habitat structure, absolute precision and accuracy might not be as important as it would be with wanting to establish plant below ground biomass derived from above ground biomass (13) or other volume critical measurements (58). Alongside the aforementioned, there are some more useful general principles for data collection which can be applied to any and all SfM-MVS projects; Collect data with as high an overlap as is practicable – Nearly every SfM-MVS software will have its own guidelines for the amount of side and forward overlap between images, these range from 60%/60% (63) to 60%/80% (64), though recent studies have shown that higher overlap, upto 90% in both side and forward, is better for accuracy and precision within SfM-MVS derived data (65). Collect both nadir and oblique imagery - James and Robson (66) demonstrated that nadir - that is looking straight down - aerial images captured via drone, along with inherent lens distortion of a camera, can induce a systematic error in the form of a doming effect in DEMs.…”
Section: Collection Of Datamentioning
confidence: 99%
“…Collect both nadir and oblique imagery - James and Robson (66) demonstrated that nadir - that is looking straight down - aerial images captured via drone, along with inherent lens distortion of a camera, can induce a systematic error in the form of a doming effect in DEMs. Cunliffe et al (13) have shown that incorporating oblique imagery can help improve the accuracy of SfM-MVS derived DTMs, whilst Nesbit and Hugenholtz (65) have gone on to quantify that incorporating oblique imagery between 20–35° from nadir, along with higher overlap can improve both precision and accuracy by up to 50%. Collect data over a wider area than is required – SfM-MVS data quality deteriorates towards the edges of a reconstruction. Making sure your AOI (area of interest) is central within the data set will ensure there is enough overlap and subsequently be of higher quality (60).…”
Section: Collection Of Datamentioning
confidence: 99%
See 1 more Smart Citation